Stochastic Eulerian field method for radiative heat transfer in a propane oxygen-enhanced turbulent diffusion flame. Issue 1 (2nd January 2017) - Nmira, Fatiha; Burot, Daria; Consalvi, Jean-Louis
Abstract : The stochastic Eulerian field (SEF) method is applied to solve the transport equation of the joint probability density function (PDF) of mixture fraction, enthalpy defect, scalar dissipation rate and soot quantities in order to predict radiative heat transfer from sooting turbulent jet diffusion flames. The flow field is computed by solving the Favre-averaged Navier–Stokes equation coupled with the standard k-ϵ model and a steady laminar flamelet (SLF) model. The modelling of soot production is carried out by using a flamelet-based semi-empirical acetylene/benzene soot model. Radiative heat transfer is modelled by using a wide-band correlated-k model and turbulent radiation interactions (TRIs) are accounted for by using the optically thin fluctuation approximation (OTFA). The model is applied to simulate an oxygen-enhanced jet turbulent diffusion flame fuelled by propane. Predicted soot volume fraction, radiant wall heat flux distributions and radiant fraction are in good agreement with the experimental data. A special emphasis was put on the evolution of the cross correlations between soot volume fraction and temperature and mixture fraction and enthalpy defect over the flame. Model results show that the former is strongly negative in regions where soot radiation is significant, which may affect turbulence–radiation interaction. The analysis of the latter showed that mixture fraction and enthalpy defect are strongly correlated over the flame. Propane flames with the same injection characteristics and different oxygen index were considered, showing that the conclusions drawn for these correlations can be generalised to flames with different sooting propensity.